Workshop Penggunaan Moodle Bagi Guru SMKN 1 Tapung - Zulfah; Layli Maydawati; Sri Yulianti; Muhammad Tresno; Daratul Aini Gaho; Darmadi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
This community service is carried out at SMK Negeri 1 Tapung. The aim of this community service activity is to provide teachers with knowledge and skills in creating e-learning using Moodle as well as creating learning media into e-learning that has been created to help the learning process. In this way, it is hoped that teachers will be able to optimize existing ICT facilities in schools. The mechanism for implementing activities in general is in the form of planning/preparation, implementation, observation and evaluation, and reflection. The result is that all teachers already know how to use e-learning moodle and create subjects, teacher profiles, upload materials, and create questions in e-learning at SMKN 1 Tapung.